Design and Development of Flow Analyzer for Peak Inspiratory Flow (PIF) and Peak Expiratory Flow (PEF) Parameters - Pambudi, Andri Lazuardi Wahyu; Yulianto, Endro; Wakidi, Levana Forra (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2023)
This research study focused on the development and testing of a flow analyzer for monitoring the PIF (Peak Inspiratory Flow) and PEF (Peak Expiratory Flow) parameters in patients undergoing mechanical ventilation. These parameters are crucial for managing respiratory diseases like asthma and COPD. The study aims to ensure the accuracy of ventilator information provided to users by periodically testing and calibrating the ventilator using the flow analyzer. The primary contribution of this research is the utilization of the AFM3000 flow sensor to measure PIF and PEF parameters. By using this sensor, the researchers intend to enhance the accuracy of ventilator readings. The study was conducted in Volume Control (VC) mode with various VT (Tidal Volume) settings, ranging from 200 to 600 mL. Two different methods of data collection were employed to gather two sets of data. From the first data collection, the largest discrepancies in reading PIF and PEF values were found to be 3.49% and 2.99%, respectively. In the second data collection, the sensor exhibited a consistent reading for a constant flow of ±0.1 LPM (Liters Per Minute), indicating stability. The research findings suggest that the AFM3000 flow sensor demonstrates good accuracy and stability in measuring PIF and PEF parameters. Furthermore, the sensor is sensitive and has a minimal delay, making it suitable for real-time graph display in the module. Overall, this study contributes to the field of medical technology by developing and validating a flow analyzer for monitoring PIF and PEF parameters in mechanical ventilation. The research showcases the potential of the AFM3000 flow sensor to improve the accuracy and reliability of ventilator information, ultimately benefiting patients with respiratory disorders.